The evolution of Indonesian curriculum: Hypothetical learning trajectory for mastery of mathematical and computational thinking - Firmasari, Siska; Tatang Herman; Elah Nurlaelah (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, Universitas Muhammadiyah Surakarta, 2023)
Some conditions are unconcerned with students believing they are learning mathematics. Students' disinterest increases when the situation is online learning due to the COVID-19 pandemic. In that case, fully online learning reduces students' mathematical and computing abilities. Therefore, this study aims to obtain a hypothetical learning trajectory in mathematics learning in constructing the skills to master mathematical and computational thinking for secondary school students. This study used part of the research development method of validation research which focuses on Hypothetical Learning Trajectory (HLT). The preparation of the HLT focuses on mastering the mathematical and computational thinking skills of junior high school students using teaching materials, learning media, and evaluation instruments on rank number and square roots materials. The subjects in this study were 30 junior high school students in class IX who took mathematics classes. The series of activities and forms of student learning assumptions become one complete trajectory for the purpose of learning achievement. A Hypothetical Learning Trajectory (HLT) was developed based on the findings of an analysis of the activities of the Junior High School Mathematics curriculum suite and PISA 2021, test results, initial observations during the learning process, and interviews with students and teachers. HLT preparation has an impact on creating learning designs that are ready to be continued at the implementation stage in the following class.